A novel smartphone scleral‐image based tool for assessing jaundice in decompensated cirrhosis patients. Issue 2 (4th January 2023) - Kazankov, Konstantin; Nixon‐Hill, Miranda; Kumar, Rahul; Amin, Ahmed; Alabsawy, Eman; Chikhlia, Anmol; Leung, Terence S.; Mookerjee, Rajeshwar P.
Abstract: Background and Aim: Serum bilirubin is an established marker of liver disease. Reliable tools for non‐invasive assessment of jaundice in cirrhosis patients, at risk of clinical decompensation, are highly desirable. While smartphone‐based imaging has been described in neonatal jaundice, it has not been investigated in advanced cirrhosis patients. Methods: We included 46 hospitalized patients with acute cirrhosis decompensation and jaundice. Scleral images using an Android smartphone were taken to derive "Scleral Color Values (SCV), " which were matched with same day serum bilirubin measurements. In 29 patients, repeat SCV and bilirubin measurements were performed over time. We analyzed the relationship of SCV and its dynamics with serum bilirubin, clinical scores, and patient outcomes. Results: Of 46 patients, 26 (57%) had alcoholic hepatitis as the decompensation precipitant. Seven patients died during admission; a further 12 following hospital discharge. SCV had an excellent linear correlation with serum bilirubin (rho = 0.90, P  < 0.001); changes in SCV and serum bilirubin across different time points, were also closely associated (rho = 0.77, P  < 0.001). SCV correlated significantly with CLIF Consortium Acute Decompensation score (rho = 0.38, P  < 0.001) and grade of Acute‐on‐Chronic Liver Failure (rho = 0.42, P  = 0.039). SCV was higher in patients who died, however, not significantly (86.1 [IQR 83.0–89.7] vs 82.3 [IQR 78.5–83.3], P  = 0.22). The associations of SCV with clinical parameters mirrored those of serum bilirubin. Conclusion: Smartphone‐based assessment of jaundice shows excellent concordance with serum bilirubin and is associated with clinical parameters in acute cirrhosis decompensation. This approach offers promise for remote assessment of cirrhosis patients at‐risk of decompensation, post hospital discharge.